„Najtrudniej opisywać to co najważniejsze”. O Płynie Lugola Bohdana Zadury - Opacka-Walasek, Danuta (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The starting point for the interpretation of the poem Płyn Lugola, [Lugol’s solution] written by B. Zadura, is the rift between the classical form of the sonnet and the title that prompts the interventionist character of the poem and that indicates journalistic involvement in and the implications of the events in Chernobyl. This in turn leads to identification of further structural tensions and dissonances (in the verse course, at the level of imaging and in shaping the mood of the poem). The descriptive category for the essence of the composition and underlined overtones of the work is the sublime, in particular as it is viewed by modern aesthetics (proposed by Lyotard, Derrida, but also Burke). What surfaces is the microscale of imaging clashed with the macroscale phenomena formalized in lyrical situation, violation of the substance of the world, stability encroached by liquidity. A particularly validated layer of the work is the sound structure of the poem: in the finely and precisely controlled instrumental line, almost equivalent to the anagram, connotes the word “Chernobyl”, though the word is not expressed explicitly in the text. The interpretation intends to prove that the stake here is the articulation of sublimity charged and permeated with a metapoetic reflection – and that “the most important is, at the same time, the most difficult to describe”.